Antioxidant, Protein, and Fat of Chicken Nuggets with the Addition of Goat Gelatin - H. Hasma; Muhammad Ali; Made Sriasih; Anwar Rosyidi; Ratmawati Malaka (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
This study aims to determine the antioxidant, protein, and fat content of chicken nuggets through the addition of goat skin and bone gelatin which was previously pretreated with Lactobacillus plantarum 1UHCC and acetic acid. Data were processed using a completely randomized design (CRD) and tested further using Duncan's test with treatments including chicken nuggets with the addition of skin gelatin through Lactobacillus plantarum pretreatment (CGSP), chicken nuggets with the addition of skin gelatin through acetic acid pretreatment (CGSA), chicken nuggets with the addition of bone gelatin through Lactobacillus Plantarum pretreatment (CGBP), chicken nuggets with the addition of bone gelatin through acetic acid pretreatment (CGBA) and control (without adding gelatin), the treatment was repeated 4 times. The results of this study were the highest antioxidant in chicken nuggets, namely with the addition of L. plantarum pretreatment gelatin, which was 20.82%, while the protein content was 57.58%, while the highest fat content was in chicken nuggets with the administration of acetic acid pre-treated goat bone gelatin (CGBA) 3.41%. This study concluded that chicken nuggets with the addition of L. plantarum gelatin pretreatment contained higher antioxidants than the control.